Use of Internet Tools and Services by Research Scholars of the University of Kerala - Divya, L. R.; Pillai Sudhier, K. G. (Journal of Information and Knowledge, 2015)
This paper focuses on the use of internet tools and services by research scholars of the faculty of applied sciences in the University of Kerala. Questionnaire method was employed for data collection and out of the 59 respondents, 41 are female and 18 male scholars. Majority of the research scholars were under the age group of 26-30. The study revealed that majority of the research scholars use internet for e - journal access and research purpose. Most of them access internet from departments, and spent more time for internet access (mean value 2.46). Results indicated that e- mail is the most commonly used web service among research scholars. Most of the time they use internet for organizing and maintenance of information. It is evident that Google, Yahoo, and Alta vista are the most widely used search engines. The study also revealed that major obstacles faced by research scholars are overload of information and distraction from the initial purpose for accessing the Internet.